2017
DOI: 10.1038/srep39833
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen sensitive self-decision making engineered CAR T-cell

Abstract: A key to the success of chimeric antigen receptor (CAR) T-cell based therapies greatly rely on the capacity to identify and target antigens with expression restrained to tumor cells. Here we present a strategy to generate CAR T-cells that are only effective locally (tumor tissue), potentially also increasing the choice of targetable antigens. By fusing an oxygen sensitive subdomain of HIF1α to a CAR scaffold, we generated CAR T-cells that are responsive to a hypoxic environment, a hallmark of certain tumors. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
143
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 37 publications
0
143
1
1
Order By: Relevance
“…Proteases that are commonly active in the tumor microenvironment can cleave the linker and disengage the masking peptide, thereby enabling CARs to be functional at the local tumor sites. An oxygen-sensitive CAR designed by fusing an oxygen-sensitive subdomain of HIF1α to a CAR scaffold generated CAR-T cells that are responsive to a hypoxic environment, a hallmark of certain tumors, which allows the CAR-T cells to only be effective at local tumor sites [76] . Indeed, in vitro models showed that the CAR surface expression and cytolysis of CAR-T cells were controlled by the oxygen concentration.…”
Section: Improvements In Safetymentioning
confidence: 99%
“…Proteases that are commonly active in the tumor microenvironment can cleave the linker and disengage the masking peptide, thereby enabling CARs to be functional at the local tumor sites. An oxygen-sensitive CAR designed by fusing an oxygen-sensitive subdomain of HIF1α to a CAR scaffold generated CAR-T cells that are responsive to a hypoxic environment, a hallmark of certain tumors, which allows the CAR-T cells to only be effective at local tumor sites [76] . Indeed, in vitro models showed that the CAR surface expression and cytolysis of CAR-T cells were controlled by the oxygen concentration.…”
Section: Improvements In Safetymentioning
confidence: 99%
“…Additionally, small molecules can be used to induce the transcription of the transgene [297] or the dimerization and assembly of split CAR chains [298]. Induction of CAR function was also exemplified in the case of a HIF-CAR which was design to incorporate HIF1α domain making it sensitive to oxygen and degraded under normoxia conditions [299]. Also, receptor potentiation by proteolysis of a small masking tag degraded in the presence of specific proteases expressed in the tumor microenvironment was elegantly demonstrated for an EGFR-specific CAR [300].…”
Section: Control Of Transgene Expression and T-cell Functionmentioning
confidence: 99%
“…Another feature of the tumour microenvironment that can be explored for context-dependent activation of CARs is the hypoxic milieu generated by inadequate tumour vascularization 95 . This feature has been taken advantage of by the design of a CAR with oxygen-sensitive domains that is degraded in normoxic conditions but remains stabilized in hypoxic conditions 96 . Although the surface expression of this construct was low and the system had a limited dynamic range, it nevertheless demonstrates that the concept of engineering T cells with microenvironmental sensors can enable control over their activity.…”
Section: Nature Biomedical Engineeringmentioning
confidence: 99%